Photodetector Architecture for Open Circuit Voltage Operation of MWIR InAsSb Detectors - Specht, Teressa; Taghipour, Zahra; Ronningen, Theodore J.; Fragasse, Roman; Tantawy, Ramy; Smith, Shane; Fuller, Earl; Khalil, Waleed; Krishna, Sanjay (2019 IEEE Research and Applications of Photonics in Defense Conference (RAPID), 2019)
Unlike conventional detectors that rely on photocurrent, the open circuit voltage photodetector architecture relies on a detector operating in zero bias. The output from the detector is coupled to the gate of a FET in sub-threshold region. Radiometric characterization of this detector will be discussed.